Building Bridges and Breaking Boundaries: Modernity and Agoraphobia - Joshua Holmes (Opticon1826, 2006)
The material function of a bridge is to facilitate movement – of vehicles, goods and services, military hardware and people. Symbolically, the bridge is a connector and therefore a triumphant emblem of modernity. But the converse of connection is the breaking, or even transgressing, of boundaries. The bridge is a boundary breaker; an intrusion into bounded space. This paper argues that inherent in modernity is the breaking and remaking of boundaries. This can lead to psychological strain, of which agoraphobia is a manifestation. For the makers and celebrators of modernity the bridge was a symbol of progress, but for critics it represented the inhumanity of ‘progress’, and for individual agoraphobics, terror.
Keywords: agoraphobia